Low-parametric modeling of Mw8.3 Illapel 2015, Chile earthquake - Bollini, María Celeste (2017)
The Mw 8.3 (GCMT) Illapel megathrust earthquake is investigated. The objective is to find out which features of the previously published rupture scenarios can be resolved using a regional strong-motion network and source models with few parameters only. Low-frequency waveforms (<0.05 Hz), at nine stations (Centro Sismológico Nacional, Chile - CSN), are subjected to modeling. Various representations of the source are used: (i) Multiple-point-source models based either on iterative deconvolution or simultaneous inversion of source pairs, (ii) Models of circular and elliptical uniform-slip patches, employing synthetic and empirical Green’s functions, respectively. This variety of methods provides consistent results. The earthquake appears to be a segmented rupture progressing from an early (deep) moment release to a later (shallow) one, towards the NW. The source models of slip-uniform patches synchronously suggest a low rupture speed 1-2 km/s. Despite different data sets and methods, this estimate of rupture speed is consistent with independent publications. As for ambiguity in literature regarding depth and timing of the rupture, our paper clearly prefers the models including a ~20-30 s delay of the shallow moment release compared to the initial deep one. The strong-motion data set and low-parametric models proved to be competitive with more sophisticated approaches. This result implies a need to improve regional accelerometer networks in South America, which might eventually help in resolving source process of possible future large events, e.g. in Patagonia.